Effect of polycaprolactone nanocapsules loaded with essential oils on biofilm formation by Staphylococcus aureus strains isolated from bovine mastitis cases - Gabriela Suthovski; Alcione Santa Catarina; Diana Paula Perin; Rubiana Mara Mainardes; Karina Ramirez Starikoff; André Lazarin Gallina; Maiara Garcia Blagitz Azevedo; Fabíola Dalmolin; Luciana Velasques Cervo; Dalila Moter Benvegnú (Universidade de São Paulo, 2023)
Abstract Bovine infectious mastitis is largely resistant to antibacterial treatment, mainly due to mechanisms of bacterial resistance in the biofilms formed by Staphylococcus aureus. Melaleuca (MEO) and citronella essential oils (CEO) are promising agents for reducing or eliminating biofilms. Free melaleuca oil presented a medium Minimum Inhibitory Concentration (MIC) of 0.625% and a Minimum Bactericidal Concentration (MBC) of 1.250%, while free citronella oil showed medium MIC and MBC of 0.313%. Thus, free CEO and MEO demonstrate bacteriostatic and bactericidal potential. We generated polymeric nanocapsules containing MEO or CEO and evaluated their efficacy at reducing biofilms formed by S. aureus. Glass and polypropylene spheres were used as test surfaces. To compare the responses of free and encapsulated oils, strains were submitted to 10 different procedures, using free and nanoencapsulated essential oils (EOs) in vitro. We observed no biofilm reduction by MEO, free or nanoencapsulated. However, CEO nanocapsules reduced biofilm formation on glass (p=0.03) and showed a tendency to diminish biofilms on polypropylene (p=0.051). Despite nanoencapsulated CEO reducing biofilms in vitro, the formulation could be improved to modify the CEO component polarity and, including MEO, to obtain more interactions with surfaces and the biofilm matrix.